The effect of altitude and travel on rugby union performance: analysis of the 2012 super rugby competition - George, T. M.; Olsen, P. D.; Kimber, N. E.; Shearman, J. P.; Hamilton, J. G.; Hamlin, M. J. (The Journal of Strength and Conditioning Research, 2015)
The aim of this study was to investigate whether playing rugby at altitude or after travel (domestic and international) disadvantaged teams. In a retrospective longitudinal study, all matches (N = 125) played in the 2012 Super Rugby Competition were analyzed for key performance indicators (KPI) from coded game data provided by OPTA sports data company. Matches were played in a home-away format in New Zealand, South Africa, and Australia. Teams based at sea level but playing at altitude (1,271-1,753 m) were more likely to miss tackles (mean ± 90% confidence interval, 1.4 ± 1.7) and score fewer points in the first half compared with games at sea level. In the second half of games, sea level teams at altitude were very likely to make fewer gain lines (-4.0 ± 2.7) compared with the second half of games at sea level. The decreased ability to break the defensive line, which may be the result of altitude-induced fatigue, could reduce the likelihood of scoring points and winning a game. Travel also had an effect on KPI, where international travel resulted in more missed tackles (1.7 ± 1.3) and less frequent gain lines (-3.0 ± 1.9) in the first half relative to matches at home; overall, away teams (domestic and international) scored 4 less points in the second half compared with home teams. In conclusion, playing away from home in another country, particularly at altitude, can have a detrimental effect on KPI, which may affect the overall performance and the chances of winning matches.